Is Universal Screening Necessary? Incidence of Tuberculosis among Tibetan Refugees Arriving in Calgary, Alberta. (29th December 2016) - Lim, Rachel; Jarand, Julie; Field, Stephen K.; Fisher, Dina
Abstract : Background . Canadian policy requires refugees with a history of tuberculosis (TB) or abnormal chest radiograph to be screened after arrival for TB. However, Tibetan refugees are indiscriminately screened, regardless of preimmigration assessment. We sought to determine the incidence of latent (LTBI) and active TB, as well as treatment-related outcomes and associations between preimmigration factors and TB infection among Tibetan refugees arriving in Calgary, Alberta. Design . Retrospective cohort study including Tibetan refugees arriving between 2014 and 2016. Associations between preimmigration factors and incidence of latent and active TB were determined using Chi-square tests. Results . Out of 180 subjects, 49 percent had LTBI. LTBI was more common in migrants 30 years of age or older (P = 0.009 ). Treatment initiation and completion rates were high at 90 percent and 76 percent, respectively. No associations between preimmigration factors and treatment completion were found. A case of active TB was detected and treated. Conclusion . Within this cohort, the case of active TB would have been detected through the usual postsurveillance process due to a history of TB and abnormal chest radiograph. Forty-nine percent had LTBI, compared to previously quoted rates of 97 percent. Tibetan refugees should be screened for TB in a similar manner to other refugees resettling in Canada.